Triaxial testing of first-year sea ice - Richter-Menge, J.A.; Cold Regions Research and Engineering Laboratory (U.S.); United States. Army. Corps of Engineers. (Hanover, N.H. : Cold Regions Research and Engineering Laboratory, 1986)
"December 1986." Bibliography: p. 32-33. Mode of access: Internet.